Fourier-like kernels as solutions of Ode's - B. D. Aggarwala (International Journal of Mathematics and Mathematical Sciences, 1995)
In this paper, we generate asymmetric Fourier kernels as solutions of ODE's. These kernels give many previously known kernels as special cases. Several applications are considered.